Webb, Justin, Duane Ireland & David Ketchen Jr. «Toward a greater understanding of entrepreneurship and strategy in informal economy». Strategy Entrepreneurship Journal, 8 (1), pp. 1-15. - Chaihuaque Dueñas, Bruno (2017)
No presenta resumen